The Effect of Assertive Communication on the Mental Health of Midwifery Students: A Communication Psychology Perspective - Elsaid, Dea Audia; Desiana, Nur Istiqamah; Alisa Rano, Jessie; Mumthi’ah Al Kautzar, Anieq (Jurnal Midwifery, 2025)
This study aims to analyze the influence of assertive communication on the mental health of midwifery students from the perspective of communication psychology. The background of this research was based on the high academic pressure and clinical practice experienced by midwifery students, which often leads to stress, anxiety, and depression. This situation necessitates effective communication strategies to maintain students’ psychological well-being during their studies. Assertive communication is considered one of the strategies that enable individuals to express their thoughts and feelings honestly and openly without harming others. This study employs a qualitative approach using data collection techniques including in-depth interviews, focus group discussions (FGD), participatory observation, and documentation. Participants were purposively sampled from midwifery students at UIN Alauddin Makassar who experienced various academic and clinical pressures. The collected data were analyzed thematically with validation through source triangulation and member checking to ensure the credibility and validity of the findings. The results show that students with passive communication styles tend to experience excessive anxiety and low self-confidence, while aggressive communication styles often trigger interpersonal conflicts that negatively affect psychological conditions. Conversely, students who apply assertive communication demonstrate higher resilience, better management of academic and clinical stress, healthy social relationships, and greater emotional stability. From the perspective of communication psychology, assertive communication functions as a protective mechanism that supports the mental health of midwifery students. This study recommends integrating assertive communication training into the midwifery curriculum as a strategic effort to enhance soft skills and support the psychological well-being of students.